PENGARUH MOTIVASI BERPRESTASI, KOMITMEN ORGANISASIONAL DAN EFIKASI DIRI TERHADAP KINERJA MANAJERIALPENGARUH MOTIVASI BERPRESTASI, KOMITMEN ORGANISASIONAL DAN EFIKASI DIRI TERHADAP KINERJA MANAJERIAL - Moh. Aliffudin (Jurnal Ilmiah Ekonomi Bisnis, 2013)
The purpose of this study was to examine the influence of achievement motivation,organizational commitment and self-efficacy on managerial performance of coursesinstitutions leader at YPA Handayani. The research method uses a survey thatinvolving 17 peoples who take through census technique. Collecting data usingquestionnaires and data analysis using multiple linear regression. The researchresults indicated that organizational commitment and self-efficacy variables havesignificant effect on managerial performance, whereas achievement motivation hasnot significant effect. Achievement motivation, organizational commitment and selfefficacysimultaneously have a significant effect on managerial performance, whichorganizational commitment has the dominant effect on managerial performance.Therefore, to improving managerial performance in courses institutions need toconsidering organizational commitment and leadership’s self-efficacy factors.